Criminalising 'the worst' part: operationalising the offence of controlling or coercive behaviour in England and Wales - McGorrery, Paul; McMahon, Marilyn (Criminal law review, 2019)
In 2015 a new offence came into effect in England and Wales: controlling or coercive behaviour in an intimate or family relationship. Three years later, similar offences were introduced in Scotland and Ireland. And it is perhaps less well known that France introduced a comparable offence in 2010 and the Australian State of Tasmania had introduced related offences of economic and emotional abuse in 2004. These offences, which criminalise non-physical abuse in domestic relationships, constitute a novel development in the criminal law, with distinctive features and challenges. This article discusses a number of legal issues that have emerged from the operation of the new offence in England and Wales. An analysis of prosecutions for controlling or coercive behaviour (235 successful convictions have been identified as of December 2018) gives some insight into special features of the offence and its impact. In the absence of primary data (such as case reports) or comprehensive secondary statistical data, media reports of cases in which people have been charged with and/or convicted of the new offence in England and Wales since it came into operation in December 2015 provide a useful basis on which to explore the operation of the offence. Our research appears to have identified about half of all successful prosecutions (107 cases) as of 28 April 2018, which was 28 months after the offence came into effect. As these reports were primarily descriptive accounts of judges’ in-court remarks, they provide an adequate basis on which to make some preliminary observations. This article identifies four legal issues that have emerged in the operation of the offence of controlling or coercive behaviour: uncertainty about which relationships are captured by the new offence; how to preserve the principle of non-retroactivity when criminalising courses of conduct (involving behaviours that may have been manifest for many years); evidentiary difficulties in criminalising courses of conduct (patterns of behaviour); and reconciling an apparent overlap between the new offence and traditional assault and threat offences.